2004
DOI: 10.1046/j.1365-2567.2004.01905.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of nitric oxide release from the human alveolar epithelial cell line A549: an in vitro correlate of innate immune response to Mycobacterium tuberculosis

Abstract: SUMMARYIn view of the presence of a large number of epithelial cells in the alveoli of the lung and their ability to produce various cytokines and chemokines, the possible role of alveolar epithelial cells in the innate immune response to tuberculosis was examined. The human alveolar epithelial cell line A549 was used as a model. The ability of A549 cells to induce nitric oxide (NO) in response to Mycobacterium tuberculosis infection was taken as an in vitro correlate of innate immunity. M. tuberculosis infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 40 publications
2
65
0
2
Order By: Relevance
“…Early studies reported that Mtb could invade and multiply in alveolar epithelial cells [4, 8], and as a consequence, these cells are thought to play a significant role in the initial immunological host response against Mtb [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Early studies reported that Mtb could invade and multiply in alveolar epithelial cells [4, 8], and as a consequence, these cells are thought to play a significant role in the initial immunological host response against Mtb [27, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…However, alveolar epithelial cells may not be a simple barrier, but respond to their microenvironment, induce various cytokines and chemokines, thus may contribute to the innate immune response during pulmonary TB (6). Indeed, infection of A549 cells with Mtb induced significant levels of nitric oxide (NO) and inducible NO synthase mRNA (6).…”
Section: Introductionmentioning
confidence: 99%
“…The cells were shown to produce NO in response to M. tuberculosis infection. Their release of NO was increased by simultaneous stimulation with a mixture of TNF-␣, IL-1␤-, and IFN-␥, resulting in mycobactericidal activity (25).…”
mentioning
confidence: 99%